(untitled) (Dimensión Empresarial, 2015)
This paper examines the relationship between the governance and the demand for international reserves in Emerging Economies (EE). The Database World Governance Indicators Project (Project WGI) available for the period 2002-2013 is employed. The main goal in this research is to examine the possible relationship between risk indicators and political stability, the strength of democratic institutions and legal regime to the accumulation of reserves in the EE in order to discern the matter to the Colombian case. Using panel data for 14 Emerging economies, it became clear how these variables of governance, the traditional determinants of the demand for international reserves and their level interrelate. The panel cointegration tests show the relationship between the behavior of political stability, strengthening of the institutions with the accumulation of international reserves of Colombia and other Emerging economies. The institutional characteristics such as corruption, political stability and violence can affect accumulation of reserves through the perception of uncertainty. The results suggest that in order to reduce the need to accumulate higher levels of reserves, Colombia could continue institutional strengthening so as to demand lower levels of reserves for precautionary reasons.